Exploring the use of information visualization for digital libraries - Zaphiris, Panayiotis; Gill, Kulvinder; Ma, Terry H.-Y.; Wilson, Stephanie; Petrie, Helen (My University, 2004)
This paper presents the findings from a study conducted to explore the current and future use of information visualization (IV) for digital libraries (DL). A series of query techniques and participatory design workshops were employed with the goal of actively involving users in identifying the key characteristics and applications of IV for DLs. The methodology employed, key findings and overall conclusions are presented and discussed.
Keywords: Cognitive systems; Computer supported cooperative work; Decision making; Graphical user interfaces; Information analysis; Software prototyping; Technical presentations; Visualization; Digital libraries